A goal-based framework on contextual requirements modelling for agent-mediated continual quality improvement (aCQI) in curriculum design - Ismail S.; Ahmad M.S. (Association for Computing Machinery, Inc, 2023)
Benchmarking; Curricula; Design; Information management; Multi agent systems; Planning; Teaching; Collective goals; Communication breakdowns; Contextual requirements; Curriculum designs; Key performance indicators; Organisational structure; Quality improvement; TROPOS methodology; Software agents